(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research investigates the impact of work-life balance and social support on turnover intention, with job satisfaction as a mediating variable. The study involved 150 employees at PT Worthfind Travel Goods Jepara, selected through purposive sampling. Data were collected via questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS 26. The results show that work-life balance has no significant direct effect on turnover intention, while social support has a significant negative effect. Both work-life balance and social support positively influence job satisfaction. Job satisfaction significantly reduces turnover intention and acts as a full mediator in the relationship between work-life balance and turnover intention, and a partial mediator between social support and turnover intention. These findings emphasize the strategic importance of enhancing employee job satisfaction to reduce turnover rates